Disaster education for Australian nursing students: An integrative review of published literature to inform curricula. Issue 1 (February 2022) - Ituma, Odira W.N.; Ranse, Jamie; Bail, Kasia; Hutton, Alison
ABSTRACT: Background: Globally, families and communities are impacted by disasters every day. Nurses are integral to assisting in disasters, in the support and enablement of individuals and communities. However, some studies indicate that nurses feel ill-equipped to assist, partially because disaster content is not thoroughly addressed in the undergraduate curriculum. Therefore, nursing schools need to equip undergraduate nursing students with the knowledge and preparation required to assist effectively during and/or following a disaster. Aim: To explore priority disaster topic areas aimed at preparing Australian undergraduate nursing students to assist in caring for survivors in the aftermath of disasters. Method: This study used an integrative review methodology. Various databases and platforms were searched for literature published between 2000 and 2018 using Medical Subject Heading terms and keywords relating to the undergraduate nursing curriculum. A thematic analysis of the included papers was conducted. Results: A total of 10 articles were identified that meet the inclusion criteria. The reviewed studies highlighted that the areas of disaster knowledge, assessment and triage, critical thinking, teamwork, technical skills, mental wellbeing, legal and ethical consideration, and socio-cultural contexts, are relevant for the undergraduate curriculum. Discussion: This review highlights disaster education and training topic areas that could be considered for inclusion in Australian undergraduate nursing curricula. The content relating to disaster assistance must be incorporated into nursing schools' curriculum. Conclusion: The incorporation of disaster-related content in the undergraduate nursing curriculum may enhance the disaster preparedness of nursing students and the nursing workforce more broadly.